Overruling rats - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The international collaborative research project STAPLERAT (Protecting staple crops in eastern Africa: integrated approaches for ecologically-based field rodent pest management), is organising the International African Small Mammal Symposium in...